2015
DOI: 10.6017/ihe.2006.45.7932
|View full text |Cite
|
Sign up to set email alerts
|

Nicaragua: New Private versus Old Private and Public

Abstract: Indeed new privates may emerge to imbue systems with a sharp privateness after old privates have evolved. Thus, the term new private means something more than just the reemergence of a private sector after a period of proscription (the prototypical post-Communist situation) and certainly more than just the emergence of new private institutions within existing private higher education sectors. Of course the exact lines between what qualifies as new private sectors are not always clear-cut.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…So in Table 6 we provide the total time for 30 trials, and in calculating percentage deviation we used the best solution found over these 30 trials. For Soto et al. (2017) the times given in their paper are the average time for each trial (Olivares, 2022), where they used 30 trials. So in Table 6 we provide the total time for 30 trials, and in calculating percentage deviation we used the best solution found over these 30 trials.…”
Section: Computational Resultsmentioning
confidence: 99%
“…So in Table 6 we provide the total time for 30 trials, and in calculating percentage deviation we used the best solution found over these 30 trials. For Soto et al. (2017) the times given in their paper are the average time for each trial (Olivares, 2022), where they used 30 trials. So in Table 6 we provide the total time for 30 trials, and in calculating percentage deviation we used the best solution found over these 30 trials.…”
Section: Computational Resultsmentioning
confidence: 99%